The Effects of Depression and Anxiety in Business Management: Iraqi Kurdistan as A Case Study - Goran Yousif Ismael; Rozhan Ali Khdir; Gizem Öneri Uzun (Engiscience Publisher, 2023)
Race, ethnicity, religion, sexual orientation, gender, and disability are just a few of the many issues that fall under the umbrella of "cultural issues." We refer to a group's beliefs and practices as having a distinct culture. In several chosen supermarkets in Iraqi Kurdistan, this study focuses on the consequences of depression and anxiety on business management about one of the cultural issues' components, gender, and potential solutions. A quantitative analysis method was implemented in this study. A literature review is also conducted to understand the obstacles and current state of knowledge while focussing on the missing knowledge gap to fill in. Therefore, the sample in this study was a collective of 200 respondents from different supermarkets in Northern Iraq from both genders. Results show that the workforce's 2-week incidence of any depressive illness in the two selected supermarkets was assessed to be very high, followed by severe depression coming in second, critical depressive disorders in incomplete recurrence or recurring (2.5%), and dysthymia (3.6%). Women were nearly twice as likely as males to have any depression, despite serious depression being significantly more regular in women. It is concluded that depression seriously damages any business management and needs to be treated to attain maximum profit gain. Business owners must include it in the business plan to provide solutions to the problems related to depression, considering gender.